(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: This article explores the epistolary novel, "Pamela" by Samuel Richardson, considered the first English novel, revolutionized literature with its focus on the psychological development of the protagonist and its exploration of themes such as social class, gender roles. Its epistolary format, provided an intimate and engaging perspective on Pamela's experiences and inner thoughts, influencing the development of the novel as a literary genre.